2014
DOI: 10.1007/s00438-014-0904-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation and transcriptome analysis of the WRKY gene family in Gossypium

Abstract: WRKY transcription factors play important roles in various stress responses in diverse plant species. In cotton, this family has not been well studied, especially in relation to fiber development. Here, the genomes and transcriptomes of Gossypium raimondii and Gossypium arboreum were investigated to identify fiber development related WRKY genes. This represents the first comprehensive comparative study of WRKY transcription factors in both diploid A and D cotton species. In total, 112 G. raimondii and 109 G. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 84 publications
4
56
0
Order By: Relevance
“…S2a), placing GhWRKY59 in the group III WRKY protein family. In G. raimondii , there are 112 putative WRKYs, which can be divided into three groups with 20 in group I, 78 in group II, and 14 in group III (Ding et al ., ). The closest orthologs of GhWRKY59 are populus ( Populus tomentosa ) PtWRKY27, cocoa ( Theobroma cacao ) TcWRKY30, soybean ( Glycine max ) GmWRKY53, tobacco ( Nicotiana tabacum ) NtWRKY53, Arabidopsis AtWRKY30, and rice ( Oryza sativa ) OsWRKY54 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…S2a), placing GhWRKY59 in the group III WRKY protein family. In G. raimondii , there are 112 putative WRKYs, which can be divided into three groups with 20 in group I, 78 in group II, and 14 in group III (Ding et al ., ). The closest orthologs of GhWRKY59 are populus ( Populus tomentosa ) PtWRKY27, cocoa ( Theobroma cacao ) TcWRKY30, soybean ( Glycine max ) GmWRKY53, tobacco ( Nicotiana tabacum ) NtWRKY53, Arabidopsis AtWRKY30, and rice ( Oryza sativa ) OsWRKY54 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Many studies have shown that WRKY gene family members are related to plant development processes, such as fiber development [16] and leaf senescence in cotton [17]. Some researchers showed that the WRKY gene family members were related to development of the embryo and anther [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The association of WRKY allelic gene expression (D t and A t ) in G. hirsutum and alternative splicing events were likewise seen in both diploid and tetraploid cotton during the developmental stage of the fiber. In summary, this study provided new results for the evolution and role of WRKY gene family in cotton species [91].…”
Section: Characterization Of Specific Genes For Cotton Fibermentioning
confidence: 68%